RNA interference for hemipteran pest control: mechanisms, resistance factors, and advances in delivery systems - Zielińska, Anna (Journal of Plant Protection Research, 2026)
RNA interference (RNAi) represents a species-specific and environmentally sustainable strategy for the control of hemipteran pests, including aphids, whiteflies, psyllids, and stinkbugs. This review integrates current knowledge on the molecular mechanisms of RNAi in insects and its translational applications in crop protection, with particular focus on host-induced gene silencing (HIGS, transgenic expression of dsRNA in planta) and spray-induced gene silencing (SIGS). The biological effects of gene knockdown – such as reduced survival, impaired development, and disrupted feeding – are discussed alongside physiological, genetic, and epigenetic factors limiting RNAi efficacy in Hemiptera. Key challenges include dsRNA degradation in the digestive tract, inefficient cellular uptake, and limited systemic spread. Recent innovations – including nanocarrier-based delivery, biodegradable formulations, and transplastomic expression – are critically evaluated. Similarly, advances in target gene identification using transcriptomic and proteomic approaches, as well as risk assessment tools for minimizing non-target effects, support the rational design of RNAi-based biopesticides. As RNAi technologies advance, their incorporation into integrated pest management strategies may facilitate species-specific, residue-free control of hemipteran pests while supporting the conservation of agroecosystem biodiversity.